Mobile App for Pre- and Intraoperative Assessment of Astigmatism Correction with Toric Intraocular Lenses in Cataract Surgery. (23rd March 2020) - Dias, Francisco Aecio Fernandes; Dias, Vinicius Jose Fernandes; Dutra, Barbara de Araujo Lima; Marques, Anna Christina Siqueira; Marçal, Edgar; Lucena, Abrahao da Rocha; Crispim Ribeiro, Joao
Abstract : Purpose . To develop a mobile app that allows capturing and editing of photographs, performs image transposition and projection of a protractor with 360° axis markings, and permits accurate visualization of programmed alignment for the positioning of toric intraocular lenses (IOLs). Methods . In this prospective case series study, a codesign methodology was chosen to develop the Eye Axis Check application. After app development, measurements were obtained and comparisons were made between manual marks and toric IOL alignment without and with the app in 30 eyes that had undergone cataract surgery with toric IOLs. The mobile app was made available to 15 ophthalmic surgeons in different cities to assess its usability. Results . The users approved the developed application for its ease of use and utility. The mean difference between the markings made manually and those made with the app was 1° (±2°; range: 0°–5°), and the mean difference between the IOL position and the assessment made by the app was 3° (±3°; range: 0°–12°). Upon comparison of the agreement between the app measurements and the manual measurements for the IOL angle, no significant differences were found, and an excellent concordance (0.997) and a strong positive linear correlation (0.995) were observed. Conclusion . A mobile app for preoperative planning and intraoperative toric IOL alignment was developed and revealed to be useful and easy to use.